What Propels Municipal Governments to Collaborate? the Case of Thematic Environmental Association in Chile - Arias-Yurisch, K; Garrido-Vergara, L (Institut za Lokalno Samoupravo in Javna Narocila Maribor, 2019)
Although it is widely accepted that inter-local agreements can enhance municipal governments’ capacity to provide complex services, there is little evidence in the Latin American case to explain why municipalities decide to collaborate with each other. What propels municipal governments to collaborate? Using data from Chilean government this paper identifies and analyzes the determinants of inter-local collaboration to address environmental issues. Five logit models are used for the empirical analysis. The results show that this form of cooperation is determined by poverty, population size, municipal fiscal capacity, and the degree of urbanization of local communities. © 2019 Lex localis.